Sobre la naturalización de la lógica* - Casabán Moya, Enric (Revista de Filosofía, 2003)
This article is devoted to give reasons against the naturalization of logic, in a sense which entails a revision of this science. The paper criticizes each historical important attempt to revise logical laws – intuitionism, quantum logic, alternative logics – and also it tries to argue that the explanation problem of quantum mechanics has nothing to do with a naturalization of logic.
Keywords: philosophical naturalism; philosophy of logic; philosophy of quantum mechanics; naturalized epistemology; scientific revolutions; truth